Method for inducing resin secondary permeation based on laser CFRP interface pretreatment
By constructing composite micro-nano structures on the surface of CFRP and utilizing channels and fractal structures formed by nanosecond pulsed fiber lasers and ultrafast lasers to promote adhesive penetration, the interfacial strength and durability issues of CFRP composite materials during bonding were solved, achieving high-strength bonding effects.
Patent Information
- Application Number
- CN202511216175.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-28
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2045-08-28
AI Technical Summary
CFRP composites have fewer surface-active functional groups, lower surface energy, higher inertness, and smoother surfaces, making it difficult to bond with resin during bonding, which affects adhesive strength and durability. Traditional laser pretreatment methods are difficult to balance the rapid spreading and deep penetration of adhesives.
Nanosecond pulsed fiber lasers are used to process macroscopic flow channels on the CFRP surface, and combined with ultrafast lasers to form nano-waves or micron-scale dendritic fractal structures, forming a composite micro-nano structure. This promotes the macroscopic spreading and microscopic penetration of the adhesive, and enhances the interfacial mechanical bonding and chemical adhesion.
It significantly improves the bonding strength and durability of CFRP, achieving high-strength interfacial bonding through the combined action of mechanical locking and chemical bonding, thus solving the problems of low CFRP bond strength and poor fatigue resistance.
Smart Images

Figure CN120885876A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of composite material interface reinforcement, in particular to a method for inducing resin secondary penetration based on laser CFRP interface pretreatment. BACKGROUND
[0002] With the pursuit of structural lightweight, the "lightweight and high-strength" CFRP composite material is increasingly attracting attention in the aviation, vehicle and other industries, and the adhesive type integrated composite material structure such as secondary bonding and bonding co-curing is beneficial to obtain smooth aerodynamic shape and greatly reduce the weight of the structure, and becomes the main form in the application of composite material structure.
[0003] However, due to the small number of active functional groups on the surface of the CFRP composite material, the low surface energy and the large inertness, the surface is smooth, so it is difficult to combine with the resin during connection, which affects the bonding strength, and therefore the CFRP composite material needs to be surface treated before bonding, and the interface bonding strength and durability of the CFRP composite material are limited by the dense structure of the resin surface and the poor fiber wettability. In order to improve the interface bonding strength and durability of the CFRP composite material, the traditional laser pretreatment method is usually used, and the modified structure processed on the surface of the CFRP composite material is mainly a single layer structure, which is difficult to consider the rapid spreading and deep penetration of the adhesive, resulting in insufficient interface combination. Therefore, it is urgent to develop a method for inducing resin secondary penetration based on laser CFRP interface pretreatment to improve the interface performance. SUMMARY
[0004] In view of the deficiencies in the prior art, the purpose of the present application is to provide a method for inducing resin secondary penetration based on laser CFRP interface pretreatment, which constructs a composite micro-nano structure of "primary structure + secondary structure" on the surface of CFRP, thereby significantly promoting the macroscopic spreading and microscopic penetration of the adhesive, and enhancing the interface mechanical engagement and chemical combination ability.
[0005] To solve the above technical problems, the implementation scheme provided by the present application is to provide a method for inducing resin secondary penetration based on laser CFRP interface pretreatment, comprising the following steps: A nanosecond pulsed fiber laser is used to scan and process the CFRP substrate surface to be bonded to form a macroscopic flow channel, and by completely removing the resin layer in the channel and exposing the carbon fiber or glass fiber, a primary structure is formed, wherein the resin removal depth accounts for 10% to 30% of the total thickness of the CFRP substrate, the depth of the macroscopic flow channel is 50% to 100% of the resin removal depth, the width of the macroscopic flow channel is 100 to 500 microns, and the periodical spacing of the macroscopic flow channel is 200 to 500 microns; The macro flow channel surface is scanned by ultrafast laser to form nano corrugation or micron fractal secondary structure with a period of 400nm-1000nm; The resin adhesive is uniformly placed on the secondary structure surface of the upper and lower CFRP interfaces to obtain a CFRP-adhesive-CFRP structural joint. The CFRP-adhesive-CFRP structural joint is subjected to heat pressing treatment.
[0006] A large-size channel is processed at the bonding position of the CFRP substrate by using a nanosecond pulsed fiber laser to provide a continuous macro flow channel for the adhesive, and at the same time, the carbon fibers or glass fibers are exposed by completely removing the resin layer to avoid bubble retention, which can improve the primary penetration efficiency of the adhesive. Then, the macro flow channel surface is processed by nano corrugation or micron fractal secondary structure using ultrafast laser, and the capillary force of the nano corrugation or micron fractal secondary structure can drive the adhesive to penetrate twice, increase the effective contact area of the adhesive and the carbon fiber and resin interface, strengthen the physical anchoring and chemical bonding, and place the resin adhesive between the secondary structures arranged in the upper and lower layers. Through the hierarchical structure design of the primary and secondary structures, the macro adhesive flow channel and the micro-nano scale capillary driving structure are considered, and the depth and uniformity of adhesive penetration are improved. Through heat pressing treatment of the adhesive at the CFRP-adhesive-CFRP structural joint, the adhesive will fully fill the primary and secondary structures during the curing process, and the mechanical locking and chemical bonding will work together to achieve high-strength interface bonding.
[0007] Preferably, the machining path of the nanosecond pulsed fiber laser adopts one-way parallel line scanning or grid scanning, and the scanning interval is consistent with the diameter of the laser focused spot used, ensuring that the resin on the CFRP surface is completely removed, so that the carbon fibers or glass fibers are exposed; after scanning, the scanning interval and number of nanosecond pulsed fiber laser are changed according to the width and period of the required macro flow channel, which is used to process the specific macro flow channel with the required size.
[0008] Preferably, in order to achieve the required primary structure processing, the parameters of the nanosecond pulsed fiber laser are as follows: The wavelength is 355nm-10.6μm, the power is 20W-150W, the pulse frequency is 1kHz-100kHz, the scanning speed is 100mm / s-1000mm / s, and the spot diameter is 50μm-100μm.
[0009] The laser energy density obtained by the parameters of the nanosecond pulsed fiber laser given herein should match the thermophysical properties of the resin and fiber on the surface of the CFRP, i.e. the laser energy density is greater than the resin damage threshold and less than the carbon fiber damage threshold, so as to ensure the removal of a specific depth of resin while not damaging the carbon fiber, to provide a macroscopic adhesive flow path and expose the carbon fiber or glass fiber surface.
[0010] Preferably, the secondary structure is a nano-ripple or micro-branch fractal structure with a periodic pitch of 5-10 microns machined on the inner wall of the primary structure groove in parallel paths, for forming a periodic nano-ripple or micro-branch fractal structure. In order to form a capillary structure that facilitates the secondary infiltration of the adhesive, a pitch less than 5-10 microns would be limited by the machining process and cannot be achieved, and a pitch greater than 5-10 microns would not form the desired capillary effect.
[0011] Preferably, in order to achieve the desired secondary structure machining, the parameters of the ultrafast laser are: The pulse width is 50 fs-10 ps, the wavelength is 180 nm-600 nm, the power is 1 W-100 W, the pulse frequency is 100 kHz-5000 kHz, the scanning speed is 1000 mm / s-4000 mm / s, and the spot diameter is 20 microns-40 microns. To enhance the capillary effect and promote the secondary infiltration of the adhesive.
[0012] Preferably, characterized in that the scanning angles of the nanosecond pulsed fiber laser and the ultrafast laser are adjusted according to the layup direction of the CFRP matrix to avoid mechanical cutting of the carbon fiber and ensure structural integrity.
[0013] Preferably, the resin adhesive is the same resin system as the CFRP matrix resin, when the CFRP matrix is epoxy resin, the adhesive is epoxy resin; when the CFRP matrix is bismaleimide resin, the adhesive is bismaleimide resin.
[0014] Preferably, the CFRP matrix is a thermoset composite material composed of epoxy resin or phenolic resin and carbon fiber or glass fiber.
[0015] Preferably, the parameters of the hot-pressing curing process are: The curing temperature rise rate is 0.5-3℃ / min; the curing holding time is 120-150 min, the curing temperature is 178℃; the curing pressure is 0.05-0.3 MPa; the cooling rate is 0.5-3℃ / min, and the cooling temperature is below 70℃.
[0016] Under the pressure and heat of the hot press, the adhesive melts, and quickly fills through the macro flow channel of the primary structure, and realizes deep penetration through the capillary force driving of the secondary structure, significantly enhances the CFRP-CFRP interface bonding strength, so that the adhesive fully fills the primary structure and the secondary structure in the curing process, and realizes high-strength interface bonding by the combined action of mechanical locking and chemical bonding.
[0017] Preferably, the thickness of the resin adhesive is 0.15mm-0.7mm.
[0018] The specific thickness of the resin adhesive can make the adhesive completely penetrate into the processed structure after melting, so that the joint place and the matrix become an integral whole, if the thickness is too thick, the joint place will form a matrix-resin-matrix structure, the strength of the resin is not enough, so the strength of the joint is not high, and if the thickness is too thin, the glue is not enough, and the microstructure cannot be fully filled, so the joint strength will also be reduced.
[0019] Compared with the prior art, the beneficial effects of the present application are that: The present application processes the primary structure with macro flow channel on the CFRP surface to be bonded by nanosecond laser, the primary structure provides fast and continuous macro flow channel for the adhesive, at the same time, the carbon fiber is exposed by completely removing the resin layer, avoiding bubble retention, improving the primary penetration efficiency of the adhesive, and then the secondary structure of nanometer ripples or micron dendritic fractals is obtained on the surface of the primary structure with macro flow channel by ultrafast laser, that is, the composite micro-nano structure is formed on the CFRP surface to be bonded, which is beneficial to the secondary penetration of the adhesive driven by capillary force, increases the effective contact area of the adhesive and the carbon fiber or glass fiber and the resin interface, strengthens the physical anchoring and chemical bonding, and finally improves the bonding strength of CFRP under the combined action of the composite structure.
[0020] The resin adhesive is uniformly placed between the upper and lower two layers of spliced secondary structures, and the structure joint of CFRP-adhesive-CFRP is obtained, so as to significantly promote the macro spreading and micro penetration of the adhesive, the adhesive at the structure joint of CFRP-adhesive-CFRP is treated by heat pressing, the adhesive fully fills the primary structure and the secondary structure in the curing process, and high-strength interface bonding is realized by the combined action of mechanical locking and chemical bonding, and finally the bonding strength of CFRP is improved under the combined action of the composite structure.
[0021] The CFRP interface enhancement pretreatment method based on laser-induced resin secondary penetration provided by the present application has reasonable process design, strong operability and wide application range, can effectively solve the problems of low connection strength and poor fatigue resistance of CFRP bonding parts, and can realize high-load and long-time safe operation of CFRP bonding components. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 This is a schematic cross-sectional view of the CFRP adhesive surface with "primary structure + secondary structure" disclosed in the embodiments of the present invention.
[0023] Figure 2 This is a schematic diagram of the cross-section of a CFRP adhesive joint implemented using the technology disclosed in an embodiment of the present invention.
[0024] Figure 3 The cross section of the CFRP adhesive joint implemented using this technology is disclosed in the embodiments of the present invention.
[0025] Figure 4 This is a comparison of the CFRP bonding performance before and after treatment in Example 1 and Comparative Example 1.
[0026] The attached figures are labeled as follows: 1. CFRP matrix; 11. Carbon fiber; 12. Resin; 13. "Primary + Secondary" structure; 2. CFRP-bondant-CFRP structural joint; 21. CFRP matrix in the joint; 22. Resin adhesive; 3. CFRP bonded sample; 31. CFRP matrix in the bonded part; 32. Bonded cross section. Detailed Implementation
[0027] To make the above-mentioned objectives, features, and advantages of the embodiments of the present invention more apparent and understandable, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in Embodiments 1 to 3, preferred embodiments are described in this invention to avoid redundancy. However, this invention is not limited to these, but can be specifically implemented in other ways within the scope of the technical solutions defined in the appended claims.
[0029] The technical solution of the present invention will be further illustrated below with specific examples.
[0030] In the following embodiments, unless otherwise specified, the methods described are conventional methods, and the reagents described are commercially available unless otherwise specified.
[0031] The method for inducing resin secondary penetration based on laser CFRP interface pretreatment provided by the application is to process upper and lower layered secondary composite structures at the position of the CFRP bonding joint, so as to improve the primary penetration efficiency of the adhesive in the CFRP bonding process, drive the adhesive to perform secondary penetration by capillary force, increase the effective contact area of the adhesive and the carbon fiber and resin interface, strengthen physical anchoring and chemical bonding, and thus realize high-strength CFRP bonding.
[0032] The CFRP matrix used in the following examples is a thermosetting composite material composed of epoxy resin or phenolic resin and carbon fiber or glass fiber, wherein the epoxy resin or phenolic resin and the carbon fiber or glass fiber can be combined in any manner. The CFRP matrix used in the following examples is a carbon fiber reinforced epoxy resin matrix composite material. In addition, the resin adhesive can be selected according to actual needs. The resin adhesive given in the present example is Loctite EA7000 050N WAERO resin adhesive.
[0033] Example 1 A method for inducing resin secondary penetration based on laser CFRP interface pretreatment, comprising the following steps: A nanosecond pulsed fiber laser with a wavelength of 355 nm, a power of 20 W, a pulse frequency of 1 kHz, a scanning speed of 100 mm / s, and a spot diameter of 50 μm is used to perform unidirectional parallel line scanning on the position to be bonded of the carbon fiber reinforced epoxy resin matrix composite material 1, forming a macro-flow channel. After scanning the resin layer in the channel to a predetermined thickness of resin removal thickness for one or more times, the resin 12 is completely removed to expose the surface of the carbon fiber 11, and a primary structure with a macro-flow channel is obtained. The depth at which the resin 12 is completely removed is 10% of the thickness of the carbon fiber reinforced epoxy resin matrix composite material 1, the depth of the macro-flow channel is 50% of the resin removal depth, i.e. 2 mm thick resin, and then the laser parameters described above are used to process the channel to be formed. The width of the macro-flow channel is 100 μm, the period of the macro-flow channel is 200 μm, and the channel array with a depth of 1 mm is as shown in Figure 1 .
[0034] An ultrashort laser with a pulse width of 50 fs, a wavelength of 180 nm, a power of 1 W, a pulse frequency of 300 kHz, a scanning speed of 1000 mm / s, and a spot diameter of 20 μm is used to perform parallel path scanning on the surface of the macro-flow channel to form a secondary structure of nanometer ripples or micron-level dendritic fractals with a period of 400 nm. The periodic processing pitch of the nanometer ripples or micron-level dendritic fractals in the secondary structure is 5 μm, and a "primary + secondary" structure 13 is obtained.
[0035] Loctite EA7000 050N WAERO resin adhesive 22 was uniformly placed on the surface of the two-level structure arranged in the upper and lower two layers, to obtain a CFRP-adhesive-CFRP structure joint 2, wherein the thickness of the Loctite EA7000 050N WAERO resin adhesive 22 was 0.15 mm. The structure without uniformly placing the Loctite EA7000 050N WAERO resin adhesive 22 in the CFRP-adhesive-CFRP structure joint 2 was the CFRP matrix 21 in the joint, as shown in Figure 2 .
[0036] The CFRP-adhesive-CFRP structure joint was cured under a curing pressure of 0.05 MPa, with a temperature rising rate of 0.5 ℃ / min from room temperature to 178 ℃, and then cooled from 178 ℃ to 70 ℃ at a rate of 0.5 ℃ / min after curing for 120 min, to obtain a CFRP bonding sample 3, as shown in Figure 3 (a), as shown in Figure 3 (b) is a cross-sectional view of 3(a), wherein 31 is the CFRP matrix in the bonding sample, and 32 is the bonding cross section.
[0037] Example 2 A method for inducing resin secondary penetration based on laser CFRP interface preprocessing, comprising the following steps: A nanosecond pulsed fiber laser with a wavelength of 1064 nm, a power of 80 W, a pulse frequency of 20 kHz, a scanning speed of 500 mm / s, and a spot diameter of 80 μm was used to perform unidirectional parallel line scanning on the position to be bonded of the carbon fiber reinforced epoxy resin based composite 1, to form a macro flow channel. The resin layer in the channel was scanned one or more times to achieve a predetermined thickness of resin removal thickness. After the resin 12 was completely removed to expose the surface of the carbon fiber 11, a primary structure with a macro flow channel was obtained, wherein the depth of the completely removed resin 12 was 20% of the thickness of the carbon fiber reinforced epoxy resin based composite 1, the depth of the macro flow channel was 80% of the resin removal depth, and then the laser parameters were used to process the channel to be formed. The width of the macro flow channel was 200 μm, the period of the macro flow channel was 300 μm, and the channel array with a depth of 1 mm was formed.
[0038] An ultrashort laser with a pulse width of 100 fs, a wavelength of 500 nm, a power of 5 W, a pulse frequency of 100 kHz, a scanning speed of 3000 mm / s, and a spot diameter of 30 μm was used to perform parallel path scanning on the surface of the macro flow channel to form a secondary structure of nanometer ripples or micron-level dendritic fractals with a period of 800 nm. The periodic processing pitch of the secondary structure of nanometer ripples or micron-level dendritic fractals was 8 μm, and a "primary + secondary" structure 13 was obtained.
[0039] Loctite EA7000 050N WAERO resin cement 22 is uniformly placed on the surface of the two-level structure arranged in the upper and lower two layers, to obtain a joint 2 of CFRP-cement-CFRP structure, wherein the thickness of the Loctite EA7000 050N WAERO resin cement is 0.5 mm. The structure without uniformly placing the Loctite EA7000 050N WAERO resin cement 22 in the CFRP-cement-CFRP structure joint 2 is the CFRP matrix 21 in the joint.
[0040] The CFRP-cement-CFRP structure joint is cured at a curing pressure of 0.1 MPa, with a temperature rising rate of 1.0 ℃ / min from room temperature to 120 ℃, and then with a temperature falling rate of 1.0 ℃ / min from 120 ℃ to 50 ℃ to take out after curing for 130 min, to complete the curing, and to make a CFRP cement sample 3.
[0041] Example 3 A method for inducing resin secondary penetration based on laser CFRP interface pretreatment, comprising the following steps: A nanosecond pulsed fiber laser with a wavelength of 10.6 μm, a power of 150 W, a pulse frequency of 100 kHz, a scanning speed of 1000 mm / s, and a spot diameter of 100 μm is used to perform unidirectional parallel line scanning on the to-be-bonded position of the carbon fiber reinforced epoxy resin-based composite 1, to form a macro-flow channel. The resin layer in the channel is scanned one or more times to achieve a predetermined resin removal thickness, and after the resin 12 is completely removed to expose the surface of the carbon fiber 11, a primary structure with a macro-flow channel is obtained, wherein the depth of the completely removed resin 12 is 30% of the thickness of the carbon fiber reinforced epoxy resin-based composite 1, the depth of the macro-flow channel is 100% of the resin removal depth, the width of the macro-flow channel is 500 μm, the period of the macro-flow channel is 500 μm, and the channel array has a depth of 1 mm.
[0042] An ultrashort laser with a pulse width of 10 ps, a wavelength of 600 nm, a power of 100 W, a pulse frequency of 5000 kHz, a scanning speed of 4000 mm / s, and a spot diameter of 40 μm is used to perform parallel path scanning on the surface of the macro-flow channel to form a secondary structure of nanometer ripples or micron-level dendritic fractals with a period of 1000 nm, and the periodic processing pitch of the secondary structure of nanometer ripples or micron-level dendritic fractals is 10 μm, to obtain a “primary+secondary” structure 13.
[0043] Loctite EA7000 050N WAERO resin adhesive 22 was uniformly placed between the upper and lower two CFRP substrates to be bonded to obtain a CFRP-adhesive-CFRP structural joint 2, wherein the thickness of the Loctite EA7000 050N WAERO resin adhesive 22 was 0.7 mm. The structure without uniformly placing the Loctite EA7000 050N WAERO resin adhesive 22 in the CFRP-adhesive-CFRP structural joint 2 was the CFRP matrix 21 in the joint.
[0044] The CFRP-adhesive-CFRP structural joint was cured at a curing pressure of 0.3 MPa, with a temperature rising rate of 3 ℃ / min from room temperature to 240 ℃, and then cooled at a rate of 3 ℃ / min from 240 ℃ to 60 ℃ to complete the curing, to obtain a CFRP bonded sample 3.
[0045] Comparative Example 1 A CFRP interface pretreatment method, comprising the following steps: Loctite EA7000 050N WAERO resin adhesive 22 was uniformly placed between the upper and lower two CFRP substrates to be bonded to obtain a CFRP-adhesive-CFRP structural joint 2, wherein the thickness of the Loctite EA7000 050N WAERO resin adhesive 22 was 0.7 mm. The structure without uniformly placing the Loctite EA7000 050N WAERO resin adhesive 22 in the CFRP-adhesive-CFRP structural joint 2 was the CFRP matrix 21 in the joint.
[0046] The CFRP-adhesive-CFRP structural joint was cured at a curing pressure of 0.05 MPa, with a temperature rising rate of 0.5 ℃ / min from room temperature to 178 ℃, and then cooled at a rate of 0.5 ℃ / min from 178 ℃ to 70 ℃ to complete the curing, to obtain a CFRP bonded sample.
[0047] The CFRP bonded samples of Examples 1-3 above can be prepared, and the CFRP bonded sample 3 prepared in Example 1 and the CFRP bonded sample prepared in Comparative Example 1 were subjected to experimental verification.
[0048] (I) Mechanical properties Table 1 is a tensile strength table of the CFRP bonded samples prepared in Example 1 and Comparative Example 1 The tensile strength of the CFRP bonding sample prepared in Example 1 is improved by 30% compared with Comparative Example 1, indicating that the mechanical interlocking and chemical bonding capacity of the interface is enhanced. After the resin adhesive is heated and melted, it flows into the microstructure of the processing, and after cooling and solidification, it can form a mortise and tenon structure, thereby enhancing the mechanical interlocking force of the interface; in addition, the laser will introduce polar functional groups such as hydroxyl (-OH), carboxyl (-COOH), carbonyl (C=O) on the surface of the material during processing. These functional groups can form hydrogen bonds, esterification reactions or covalent bonds with the -OH, -NH2, -COOH groups in the epoxy glue, phenolic glue, polyurethane adhesive, thereby enhancing the chemical bonding capacity.
[0049] As shown in Figure 4 Comparative Example 1, the laser-untreated sample joint breaks at a tensile force of 5000N, while the laser-treated joint prepared in Example 1 breaks at a tensile force of 6500N. The area of the joint prepared in Comparative Example 1 and Example 1 is 3cm 2 , and the tensile strength is calculated by the formula of force / area=tensile strength. Therefore, the tensile strength of the former is 16.7MPa, and the tensile strength after laser treatment is 21.2MPa. Further indicating that the laser treatment enhances the mechanical interlocking of the interface.
[0050] Obviously, those skilled in the art can make various modifications and changes to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and changes of the present application belong to the scope of the claims of the present application and their equivalent technologies, the present application also intends to include these modifications and changes.
Claims
1. A method for inducing secondary resin permeation based on laser CFRP interface pretreatment, characterized in that, Includes the following steps: Nanosecond pulsed fiber lasers are used to scan and process the CFRP matrix surface to be bonded, forming macroscopic flow channels. By completely removing the resin layer in the channels and exposing carbon fibers or glass fibers, a primary structure is formed. The resin removal depth accounts for 10% to 30% of the total thickness of the CFRP matrix, the depth of the macroscopic flow channels is 50% to 100% of the resin removal depth, the width of the macroscopic flow channels is 100 μm to 500 μm, and the periodic spacing of the macroscopic flow channels is 200 μm to 500 μm. Ultrafast lasers are used to scan the surface of macroscopic flow channels to form secondary structures with nano-waves or micron-scale dendritic fractals with periods of 400nm~1000nm. The resin binder is evenly placed on the secondary structure surface of the interface between the upper and lower CFRP layers to obtain a CFRP-binder-CFRP structural joint. The CFRP-bondant-CFRP structural joint is subjected to hot pressing curing treatment.
2. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The processing path of the nanosecond pulsed fiber laser adopts unidirectional parallel line scanning or grid scanning, and the scanning interval is consistent with the diameter of the laser focusing spot used; after scanning, the scanning interval and number of times of the nanosecond pulsed fiber laser are changed according to the width and period of the required macroscopic flow channel.
3. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The parameters of the nanosecond pulsed fiber laser are as follows: The wavelength is 355nm~10.6μm, the power is 20W~150W, the pulse frequency is 1kHz~100kHz, the scanning speed is 100mm / s~1000mm / s, and the spot diameter is 50μm~100μm.
4. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The secondary structure is formed by periodically processing nano-waves or micron-scale dendritic fractal structures with a spacing of 5μm to 10μm on the surface of the macroscopic flow channel of the primary structure using parallel paths.
5. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The parameters of the ultrafast laser are: The pulse width is 50fs~10ps, the wavelength is 180nm~600nm, the power is 1W~100W, the pulse frequency is 100kHz~5000kHz, the scanning speed is 1000mm / s~4000mm / s, and the spot diameter is 20μm~40μm.
6. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The scanning angles of both nanosecond pulsed fiber lasers and ultrafast lasers are adjusted according to the layup direction of the CFRP matrix.
7. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The resin binder and the CFRP matrix resin are from the same resin system.
8. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The CFRP matrix is a thermosetting composite material made of epoxy resin or phenolic resin and carbon fiber or glass fiber.
9. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The parameters for hot-press curing are: The curing heating rate is 0.5℃ / min to 3℃ / min; the curing holding time is 120min to 150min; the curing temperature is 120℃ to 240℃; the curing pressure is 0.05MPa to 0.3MPa; the cooling rate is 0.5℃ / min to 3℃ / min; and the cooling temperature is below 70℃.
10. The method for inducing secondary resin permeation based on laser CFRP interface pretreatment according to claim 1, characterized in that, The thickness of the resin binder is 0.15mm to 0.7mm.
Citation Information
Patent Citations
Carbon fiber reinforced resin laminated board adhesive joint and preparing method thereof
CN110202859A
Composite material and metal connecting method based on metal surface femtosecond laser etching
CN119319683A
Composite molding
JP2021120194A
Joining carbon laminates using pulsed laser irradiation
US20200290293A1